Landscape-scale research for conservation and development in the tropics: fighting persisting challenges - Pfund, J.L. (2010)
Landscape approaches have been identified as a way to address conservation and development issues in biodiversityrich tropical areas. The author conducted a literature review of 51 case studies selected by an independent analyst to evaluate how these approaches have been applied. The case studies are categorized and assessed against their objectives, scales and methods. The review highlights imbalances that favor analyses of conservation over economic outcomes and a still unmet need to provide practical solutions for analyzing the multidimensional factors affecting tropical forests at landscape scale. Applications of landscape approaches still face challenges: Simple landscape assessment tools are needed as well as a framework to allow for monitoring and comparing studies, landscape, and national initiatives. Recent research has addressed some challenges through an increased focus on learning processes and tools for adaptive landscape management.